Study on Courage Perceptions of Athletes Participating in Eastern Anatolia Turkish Senior boxing Championship Natıonal Team Selections - Serkan Zengin (Selcuk University, 2019)
The aim of this research is to compare sub-dimensions of courage scale in sports which are competence-proficiency, determination, boldness, taking risk and being self-sacrificing in sports according to various demographic values of boxers participating in senior national team selections held in Eastern Anatolia. Sample group of the study consists of 61 boxers participating in national team selections. In the research, personal information form for participants and scale of courage in sports developed by Konter and Johan (11) were used. Boxers' ages, types of residences where they live, educational status, occupations of their parents, income levels, sport ages and athlete status were compared with the sub-dimensions of the scale. SPSS 22.0 Windows program was used to analyze data obtained. As a result of normality tests, it was determined that the data were not distributed normally. Because of this reason, while non-parametric Kruskal Wallis H test was used in the study, Mann Whitney U test was used to compare sub-dimension scores of scale according to mother's educational status. Significance level was accepted as lt;0,05. As a result, for boxers participating in the selection, there was no significant difference between sub-dimensions of courage scale in sports and their ages, types of residences where they live, educational status, occupations of their parents, income levels, sport ages, athlete status.